The integrated use of borehole coal chemical technologies to produce synthetic fuel - O. S. Bryukhovetskiy; I. Y. Naydenko; N. D. Muralev; L. A. Bayramgulova (Известия высших учебных заведений: Геология и разведка, 2016)
The problem of coal mining and its processing into the high-effectual and ecologically clean fuel - synthetic gas and synthetic liquid fuel - has been investigated. The main technology of coal processing such as obtaining coal-water fuel, hydrogenation and gasification has been considered. An analysis of foreign and domestic experience for chemical methods of coal redistribution is presented. The products are the synthetic gas and synthetic liquid fuel (petrol, kerosene, diesel and jet fuel). The authors suggest an integrated coal processing technology: hydro-jet borehole technology and underground coal gasification for thin coal seams and low grade coal processing. It is also advisable for distant regions and areas with poor infrastructure. There is a possibility for creation mobile and compact complexes for coal chemical processing.